Negritude: uma identidade legal em consequência da liberdade - Brito, Luciana da Cruz (Afro-Ásia, 2021)
Resenha de: de LA FUENTE, Alejandro; GROSS, Ariela. Becoming free, becoming black: race, freedom, and law in Cuba, Virginia and Louisiana. Nova York: Cambridge University Press, 2020. 281p